2007
DOI: 10.1093/ps/86.3.444
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Condemnation Rate Analysis of Commercial Turkey Flocks Treated with a Lactobacillus spp.-Based Probiotic

Abstract: The use of defined probiotic cultures in the poultry industry has recently become more common. However, few conclusive studies regarding their efficacy under commercial conditions have been reported in the scientific literature. We conducted a study that included 118 commercial turkey hen lots, ranging from 1,542 to 30,390 hens per lot, of either Nicholas or Hybrid genetic lines, to look at the effect of a selected commercial Lactobacillus-based probiotic (FM-B11) on turkey BW, performance, and health. Sixty l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 4 publications
1
30
0
2
Order By: Relevance
“…On the other hand, Szasz, (2002), Ware and Zinn (2005) reported that Fibrozyme inclusion to the steers or heifer's diets increased total tract digestibility of NDF and ADF and increased DMI and average daily gain. Few workers concluded improved feed intake, feed conversion rate, daily weight gain and total body weight in sheep, goat and cattle on administration of DFM (Torres-Rodriguez et al, 2007;Samli et al, 2007;Casey et al, 2007). Improvement from DFM supplementation could be anticipated due to positive effects on various digestive processes, especially cellulolysis, synthesis of microbial protein, stabilizers of ruminal pH and lactate, increased absorption of some nutrients and displayed a growth-promoting effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Szasz, (2002), Ware and Zinn (2005) reported that Fibrozyme inclusion to the steers or heifer's diets increased total tract digestibility of NDF and ADF and increased DMI and average daily gain. Few workers concluded improved feed intake, feed conversion rate, daily weight gain and total body weight in sheep, goat and cattle on administration of DFM (Torres-Rodriguez et al, 2007;Samli et al, 2007;Casey et al, 2007). Improvement from DFM supplementation could be anticipated due to positive effects on various digestive processes, especially cellulolysis, synthesis of microbial protein, stabilizers of ruminal pH and lactate, increased absorption of some nutrients and displayed a growth-promoting effect.…”
Section: Discussionmentioning
confidence: 99%
“…Published experimental and commercial studies have shown that these selected probiotic organisms are able to reduce idiopathic diarrhea in commercial turkey brooding houses [73]. Large scale commercial trials indicated that appropriate administration of this probiotic mixture to turkeys and chickens increased performance and reduced costs of production [69,74,75]. These data have clearly demonstrated that selection of therapeutically efficacious probiotic cultures with marked performance benefits in poultry is possible, and that defined cultures can sometimes provide an attractive alternative to conventional antimicrobial therapy.…”
Section: Probiotics In Poultry Researchmentioning
confidence: 95%
“…Published experimental and commercial studies have shown that these selected probiotic organisms are able to reduce idiopathic diarrhea in commercial turkey brooding houses (S. E. . Large scale commercial trials indicated that appropriate administration of this probiotic mixture to turkeys and chickens increased performance and reduced costs of production (Torres-Rodriguez et al, 2007a;Torres-Rodriguez et al, 2007b;Vicente et al, 2007a;Vicente et al, 2007b;Vicente et al, 2007c). These data have clearly demonstrated that selection of therapeutically efficacious probiotic cultures with marked performance benefits in poultry is possible, and that defined cultures can sometimes provide an attractive alternative to conventional antimicrobial therapy (seehttp://www.pacificvetgroup.com/ for more information).…”
Section: Lactic Acid Bacteria-based Probiotic For Salmonella Control mentioning
confidence: 99%
“…A well-characterized LAB-based probiotic has been investigated in numerous studies Torres-Rodriguez et al, 2007a;Torres-Rodriguez et al, 2007b;Vicente et al, 2007a;Vicente et al, 2007b;Vicente et al, 2007c) and has now been commercialized (Pacific Vet Group USA Inc., Fayetteville AR 72703). Struggles with speciation of the LAB isolates during development of this product illustrate the well recognized problem for speciation of LAB.…”
Section: Comparisons Between Genotypic 16s Rrna Midi and Biolog Idementioning
confidence: 99%